Tempo and timing of ecological trait divergence in bird speciation. - McEntee,JP; Tobias,JA; Sheard,C; Burleigh,JG (Nature Ecology and Evolution, 2018)
Organismal traits may evolve either gradually or in rapid pulses, but the relative importance of these modes in the generation of species differences is unclear. Additionally, while pulsed evolution is frequently assumed to be associated with speciation events, few studies have explicitly examined how the tempo of trait divergence varies with respect to different geographical phases of speciation, starting with geographic isolation and ending, in many cases, with spatial overlap (sympatry). Here we address these issues by combining divergence time estimates, trait measurements and geographic range data for 952 avian sister species pairs worldwide to examine the tempo and timing of trait divergence in recent speciation events. We show that patterns of divergence in key ecological traits are not gradual, but instead seem to follow a pattern of relative stasis interspersed with evolutionary pulses of varying magnitude. We also find evidence that evolutionary pulses generally precede sympatry, and that greater trait disparity is associated with sympatry. These findings suggest that early pulses of trait divergence promote subsequent transitions to sympatry, rather than occurring after sympatry has been established. Incorporating models with evolutionary pulses of varying magnitude into speciation theory may explain why some species pairs achieve rapid sympatry whereas others undergo prolonged geographical exclusion.